Varietas Unggul Baru Padi untuk Mengantisipasi Ledakan Penyakit Tungro - Ladja, Fausiah T.; Widiarta, I Nyoman (Puslitbang Tanaman Pangan, 2012)
Rice tungro disease is an important disease of rice, caused by viruses, transmitted by green leafhopper. Tungro virus infection reduces rice yield up to 90%. If the plants were infected in the vegetative stage it might caused total loss. Tungro is endemic in South Sulawesi, Bali, West Java and Central Java. The outbreak might occur due to the effect of climate changes, either directly or indirectly. Higher temperatures shortens the life cycles of the insect vector and also fastens virus development. Presently, the chances of tungro disease spread to become an outbreaks are increasing. The use of resistant varieties is an alternative to control tungro disease. Resistant varieties can be categorized into green leafhoppers resistant, and virus resistant. In Indonesia, four green leafhoppers resistance genes had been used in breeding for green leafhoppers resistance, namely Glh 1, glh 4, Glh 5, and Glh 6, while recently virus resistant parent such Balimau Putih, Utri Merah, and TKM6 had been used to breed virus resistant varieties to anticipate the outbreaks of tungro disease as a result of climate changes. The newly released tungro virus resistant varieties, were: Tukad Unda, Tukad Balian, Tukad Petanu, Kalimas, Bondoyudo, Inpari 7 Lanrang, Inpari 8, and 9 Inpari Elo. Hybrid rice varieties named HiPa-3 and HiPa-4 were also reported as resistant to tungro virus. Rotational planting of green leafhopper resistant varieties could no longer be recommended in areas where green leafhopper populations had adapted to all classes of varities. Therefore the recommendation of the use of resistant varieties should be based on the varietal suitability map to the green leafhopper biotype, as well as to the virus strain.